Otimiza??o de Redes de Sensores Visuais sem Fio por Algoritmos Evolutivos Multiobjetivo - Rangel, Elivelton Oliveira (2018)
Wireless visual sensor networks can provide valuable information for a lot of moni- toring and control applications, which has driven much attention from the academic community in last years. For some applications, a set of targets have to be covered by visual sensors and sensing redundancy may be desired in many cases, especially when applications have availability requirements or demands for multiple coverage perspectives for viewed targets. For rotatable visual sensors, the sensing orientations can be adjusted for optimized coverage and redundancy, with different optimization approaches available to address this problem. Particularly, as different optimization parameters may be considered, the redundant coverage maximization issue may be treated as a multi-objective problem, with some potential solutions to be conside- red. In this context, two different evolutionary algorithms are proposed to compute redundant coverage maximization for target viewing, intending to be more efficient alternatives to greedy-based algorithms. Simulation results reinforce the benefits of employing evolutionary algorithms for adjustments of sensors? orientations, poten- tially benefiting deployment and management of wireless visual sensor networks for different applications.